Bacillus sp. strain QW90, a bacterial strain with a high potential application in bioremediation of selenite - Mohaddeseh Khalilian; Mohammad Reza Zolfaghari; Mohammad Soleimani; Mohammad Reza Zand Monfared (Islamic Azad University, 2014)
Introduction: Selenium oxyanions are toxic to living organisms at excessive levels. Selenite can interfere with cellular respiration, damage cellular antioxidant defenses, inactivate proteins by replacing sulfur, and block DNA repair. Microorganisms that are exposed to pollutants in the environment have a remarkable ability to fight the metal stress by various mechanisms. These metal-microbe interactions have already found an important role in bioremediation. The objective of this study was to isolate and characterize a bacterial strain with a high potential in selenite bioremediation. Methods: In this study, 263 strains were isolated from wastewater samples collected from selenium-contaminated sites in Qom, Iran using the enrichment culture technique and direct plating on agar. One bacterial strain designated QW90, identified as Bacillus sp. by morphological, biochemical and 16S rRNA gene sequencing, was studied for its ability to tolerate high levels of toxic selenite ions by challenging the microbe with different concentrations of sodium selenite (100-600 mM). Results: Strain QW90 showed maximum Minimum Inhibitory Concentration (MIC) to selenite (550 mM) and the maximum selenite removal was exhibited at 30 degrees C, while the activity was reduced by 20% and 33.8% at 25 and 40 degrees C, respectively. The optimum pH and shaking incubator for the removal activity were shown to be 7.0 and 150 rpm at 50.7% and 50.8%, respectively. Also, the concentration of toxic sodium selenite (800 μg/ml) in the supernatant of the bacterial culture medium decreased by 100% after 2 days, and the color of the medium changed to red due to the formation of less toxic elemental selenium. Conclusion: This study showed that the utilization of enrichment culture technique in comparison to the direct plating on agar leads to better isolation of selenite resistant bacteria. Bacterial strain was resistant to high concentrations of selenite and also it reduced selenite to red elemental selenium. Therefore, this microorganism could be further used for bioremediation of contaminated sites.